2009
DOI: 10.1002/dneu.20757
|View full text |Cite
|
Sign up to set email alerts
|

Topography of estradiol‐modulated genomic responses in the songbird auditory forebrain

Abstract: Sex steroids facilitate dramatic changes in behavioral responses to sociosexual signals and are increasingly implicated in the sensory processing of those signals. Our previous work demonstrated that in female white-throated sparrows, which are seasonal breeders, genomic responses in the auditory forebrain are selective for conspecific song over frequency-matched tones only when plasma estradiol (E2) reaches breeding levels. Here, we sought to map this E2-dependent selectivity in the best-studied area of the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
93
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(108 citation statements)
references
References 86 publications
9
93
1
1
Order By: Relevance
“…Our results for the auditory midbrain parallel a number of studies from other taxa that describe an important role for estradiol in sensory processing of social signals and of audition (Arch and Narins, 2009;Caras, 2013;Earp and Maney, 2012;Maney, 2013;Maney et al, 2006Maney et al, , 2008Maney and Pinaud, 2011;Petrulis, 2013;Remage-Healey, 2012, 2014Sanford et al, 2010;Sisneros, 2009c;Tremere et al, 2009;Walpurger et al, 2004;Yovanof and Feng, 1983). In the túngara frog, a previous study showed that hCG, which stimulates production of gonadal steroids (Lynch et al, 2006;Wu et al, 2001), increases egr-1 expression in the laminar nucleus of the torus (Lynch and Wilczynski, 2008).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Our results for the auditory midbrain parallel a number of studies from other taxa that describe an important role for estradiol in sensory processing of social signals and of audition (Arch and Narins, 2009;Caras, 2013;Earp and Maney, 2012;Maney, 2013;Maney et al, 2006Maney et al, , 2008Maney and Pinaud, 2011;Petrulis, 2013;Remage-Healey, 2012, 2014Sanford et al, 2010;Sisneros, 2009c;Tremere et al, 2009;Walpurger et al, 2004;Yovanof and Feng, 1983). In the túngara frog, a previous study showed that hCG, which stimulates production of gonadal steroids (Lynch et al, 2006;Wu et al, 2001), increases egr-1 expression in the laminar nucleus of the torus (Lynch and Wilczynski, 2008).…”
Section: Discussionsupporting
confidence: 87%
“…For example, estradiol shapes auditory tuning in midshipmen fish so that, during the breeding season, females are more sensitive to the harmonics in the calls of courting males, which enhances the adaptive coupling of the sender and the receiver for reproductive success (Sisneros, 2009a,b,c;Sisneros et al, 2004). Similar mechanisms of estradiol-dependent modulation of acoustic communication circuits are present in birds in response to plasma estradiol (Maney et al, 2006(Maney et al, , 2008Maney and Pinaud, 2011;Sanford et al, 2010) and locally produced neuroestrogens (Krentzel and Remage-Healey, 2015;Pawlisch and Remage-Healey, 2015;Remage-Healey, 2012, 2014RemageHealey et al, 2010RemageHealey et al, , 2008Remage-Healey and Joshi, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The NCM is enriched in expression of the estrogen-synthesis enzyme aromatase (Jeong et al, 2011; Saldanha et al, 2000), and it is considered analogous to mammalian secondary auditory cortex (e.g., Bolhuis and Gahr, 2006; Wang et al, 2010). NCM is key for song recognition and discrimination (Boumans et al, 2008; Gobes and Bolhuis, 2007; Sanford et al, 2010; Yoder et al, 2012) and NCM sends information into sensorimotor HVC indirectly via two distinct pathways (NIf and CLM; see Fig. 2).…”
Section: Steroids As Neuromodulators Intrinsic To the Cnsmentioning
confidence: 99%
“…A variety of studies have examined the role of E 2 manipulation on song preference, immediate early gene activity, and/or the neurophysiological activity of NCM cells in male and female zebra finches as well as seasonally-breeding birds (reviewed in Cornil et al, 2012;Maney and Pinaud, 2012;De Groof et al, 2013). For example, E 2 implants in female zebra finches result in a preference for songs with longer bouts (Clayton and Pröve, 1989), more complex songs (Vyas et al, 2009), increase extracellular multiunit activity in NCM in response to training with conspecific songs (Yoder et al, 2014), and in female white-throated sparrows (Zonotrichia albicollis) cause an increased ZENK expression in NCM, but primarily rostrally (Sanford et al, 2010). Male zebra finches implanted with testosterone -presumably aromatized by NCM neurons -learn to discriminate between their own song and the song of another conspecific in fewer trials than controls (Cynx and Nottebohm, 1992).…”
Section: Accepted Manuscriptmentioning
confidence: 99%